A four-month follow-up study of Cardiac performance in patients hospitalized with COVID-19 in a Tertiary Care Government Medical Hospital. (March 2022) - Sayed, M.A.; Guru, N.K.; Syed, H.; Nazneen, S.; Soomro, A.; Begum, S.; Khan, A.; Jaffery, S.; Sayed, S.A.
Abstract : Purpose: Myocardial injury is one of the most frequently observed injury in patients hospitalized with coronavirus disease 2019 (COVID-19) pneumonia. Cardiac abnormalities ranging from elevations of cardiac necrosis biomarkers to cardiac dysfunction associated with myocarditis has been reported during the acute COVID-19 phase. Not much information is available on late cardiac manifestations in patients who have recovered from the cute COVID-19 illness. Our purpose is to present and quantify the extent of alterations in cardiac function in patients hospitalized 4 months earlier for COVID-19 infection. Methods & Materials: A prospective echocardiographic evaluation was conducted of 39 patients hospitalized 4±1 month earlier for a laboratory-confirmed and symptomatic COVID-19. Thorough analysis of risk-factors was noted using a pre-prepared questionnaire. Echocardiographic measurements and respective cardiac investigations were analyzed using inferential and sensitivity analysis. Results: Of the 39 patients (mean age 54 ± 11 years, 73% male), twenty-seven (69%) had pre-existing cardiovascular risks factors (systemic hypertension, diabetes, or dyslipidemia), and four patients (10.3%) had a known prior myocardial infarction (MI). Seventeen patients (43.6%) experienced myocardial injury during the index COVID-19 hospitalization as identified by a rise in cardiac troponin levels. Four months later, 71.8% of patients still reported clinical symptoms including exertional dyspnea for 69%. Under resting condition, echocardiographic measurements were indifferent between patients with versus without myocardial injury during the acute phase of COVID-19 infection. On the contrary, low-level exercise (25W for 3 min) showed a significant increase in the average E/e' ratio (P < 0.01) and the systolic pulmonary artery pressure (P < 0.05) in patients with myocardial injury during the acute COVID-19 phase. Sensitivity analyses showed that these left ventricular diastolic markers changes were observed irrespective of pre-existing cardiovascular risk factors or established cardiac diseases further cementing that the SARS-CoV-2 infection was the primary cause. Conclusion: Four months after the acute COVID-19 phase, statistically significant cardiac diastolic abnormalities were observed in patients who experienced myocardial injury but not in patients without cardiac involvement.